Pakistan overprints on service post cards of British India with forms used by North Western railways (Part II) - Isani, Dr.Usman Ali (2015)
The book would typically explore the historical and philatelic significance of overprinted service postcards issued during the British Indian period, specifically those meant for government or railway use. It would detail how these overprints were utilized by the North Western Railways, perhaps illustrating their function in facilitating communication and administrative processes.
Keywords: Historical Context -- British India; Types of Overprints; Railway Operations -- Case Studies; Visual Documentation -- Philatelic Significance